IMPACT OF MERAPI SAND MINING IN KLATEN CENTRAL JAVA - Syaifulloh, Arief K. (Faculty of Law-Universitas Bandar Lampung, 2020)
In the general explanation of Law No. 4 of 2009 on Mineral and Coal Mining it isoutlined that the Basic Law 1945 Article 33 paragraph (3) affirms the earth, water, andnatural wealth contained therein is controlled by the state and used for the greatprosperity of the people. In this study, the authors examined how environmentaldamage impacts the merapi sand mining in Klaten. The research method used in thisstudy is empirical legal research, where in empirical research emphasizes more on thesymptoms and consequences that occur based on the field, or in another sense thisstudy uses observation methods as primary data to see how the law in action goes.From the results of the research obtained that the impact of merapi sand mining in thecentral java klaten is the first impact on the damage of agricultural land, plantation landthat certainly threatens the availability of land for future generations of farmers thatwill certainly have an impact on food availability, secondly damaging evacuation routesand thirdly disrupting water content, ecology, landslide prone.